Impact of antibiotic treatment on immune-checkpoint blockade efficacy in advanced non-squamous non-small cell lung cancer - Huemer, Florian; Rinnerthaler, Gabriel; Westphal, Theresa; Hackl, Hubert; Hutarew, Georg; Gampenrieder, Simon Peter; Weiss, Lukas; Greil, Richard (Oncotarget, 2018)
Despite durable responses from immune-checkpoint blockade (ICB) in a subset of patients with advanced non-small cell lung cancer (NSCLC), the majority of patients do not derive benefit from this treatment. In this analysis we evaluated the impact of concomitant administration of antibiotics during initiation of ICB on clinical outcome. Advanced non-squamous NSCLC patients receiving ICB as second- or later line between 2015 and 2017 at our tertiary cancer center in Salzburg (Austria) were included. Concomitant use of antibiotics was defined as administration of antibiotics within a time frame of one month before or one month after initiation of ICB (AB -group). Of the 30 patients included, 11 (36.7%) received antibiotics one month before or one month after start of ICB (AB -group). Median PFS on ICB was in favor of the AB -group (AB : 3.1 months [95%CI: 3.0-16.3]; AB : 2.9 months, [95%CI: 1.9-NA]; HR=0.46 [95%CI: 0.12-0.90], p=0.031). Furthermore, median OS was significantly longer in the AB -group (AB : 15.1 months [95%CI: 11.1-NA]; AB : 7.5 months [95%CI: 6.3-NA]; HR=0.31 [95%CI: 0.02-0.78], p=0.026). In a multivariate analysis, the antibiotic treatment status was identified as the only parameter statistically significantly associated with PFS (p=0.028) and OS (p=0.026). Stratification of patients according to the antibiotic treatment status is warranted in future trials investigating ICB.